Human Innate Lymphoid Cells: Their Functional and Cellular Interactions in Decidua - Vacca, Paola; Vitale, Chiara; Munari, Enrico; Cassatella, Marco Antonio; Mingari, Maria Cristina; Moretta, Lorenzo (Frontiers in Immunology, 2018)
Innate lymphoid cells (ILC) are developmentally related cell subsets that play a major role in innate defenses against pathogens, in lymphoid organogenesis and in tissue remodeling. The best characterized ILC are Natural Killer (NK) cells. They are detectable in decidua in the early phases of pregnancy. During the first trimester, NK cells represent up to 50% of decidua lymphocytes. Differently from peripheral blood (PB) NK cells, decidual NK (dNK) cells are poorly cytolytic, and, instead of IFN, they release cytokines/chemokines that induce neo-angiogenesis, tissue remodeling and placentation. dNK interact with resident myeloid cells and participate in the induction of regulatory T cells that play a pivotal role in maintaining an efficient fetal-maternal tolerance. dNK cells may originate from CD34+ precursor cells present in situ and/or from immature NK cells already present in endometrial tissue and/or from PB NK cells migrated to decidua. In addition to NK cells, also ILC3 are present in human decidua during the first trimester. Decidual ILC3 include both Natural cytotoxic receptors (NCR)+ and NCR- cells, producing respectively IL-8/IL-22/GM-CSF and TNF/IL-17. NCR+ILC3 have been shown to establish physical and functional interactions with neutrophils that, in turn, produce factors that are crucial for pregnancy induction/maintenance and for promoting the early inflammatory phase, a fundamental process for a successful pregnancy. While NCR+ILC3 display a stable phenotype, most of NCR-ILC3 may acquire phenotypic and functional features of NCR+ILC3. In conclusion, both NK cells and ILC3 are present in human decidua and may establish functional interactions with immune and myeloid cells playing an important role both in innate defenses and in tissue building/remodeling/placentation during the early pregnancy. It is conceivable that altered numbers or function of these cells may play a role in pregnancy failure.